Polyvinyl chloride foam for offshore operations and method for its production
Patent Information
- Application Number
- CN202611162555.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-08-03
AI Technical Summary
该工艺虽能提升泡沫强度,但过高的异氰酸酯用量导致体系内残留大量未反应的活性异氰酸酯基团
(1)本发明所述的海上作业用聚氯乙烯泡沫材料,以聚氯乙烯树脂为基体树脂,以硅烷改性硼酸铝纳米晶须、1-(9,10-环氧十八烷酰氧基)-3-(2-甲基丙-2-烯酰氧基)丙-2-醇以及油酸改性Mg-Al-Zn三元插层水滑石为改性原料,4,4'-二苯基甲烷二异氰酸酯与4,4'-二环己基甲烷二异氰酸酯复配构建软硬协同交联网络,提升泡沫整体强度,偶氮二甲酰胺、苯-1,3-二磺酰肼、氧化锌复配发泡剂实现梯度成核发泡,得到高闭孔低吸水泡沫,热稳定剂、光稳定剂、抗氧剂协同抑制湿热、紫外老化,保障海上长期服役稳定性。由此,原料之间协同作用,使得制备的海上作业用聚氯乙烯泡沫材料具有优异的耐盐雾性能以及抗冲击性能。
Smart Images

Figure SMS_5
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polyvinyl chloride foam material preparation technology, specifically relating to a polyvinyl chloride foam material for marine operations and its preparation method. Background Technology
[0002] Marine engineering equipment, offshore vessels, underwater exploration equipment, and floating infrastructure are increasingly used in near-shore exploration, deep-sea mining, maritime operations, and wind power maintenance. Solid buoyancy materials are the core components for achieving lightweight load-bearing capacity and constant buoyancy counterweight in these devices. Marine environments are characterized by harsh conditions such as high salt spray corrosion, continuous seawater immersion, tidal loads, wave impacts, and deep-sea hydrostatic pressure. Therefore, foam substrates require low water absorption, high impact toughness, weather resistance, corrosion resistance, and long-term service stability.
[0003] Cross-linked closed-cell PVC foam, with its advantages of wide adjustable density range, high closed-cell rate, low water absorption, and easy processing, is gradually becoming the preferred material for the core layer of near-shore special operation vessels, offshore wind power protective mats, floating dock platforms, and shallow-sea submersible equipment. Currently, the mainstream preparation route for industrially mass-produced high-strength cross-linked PVC foam is as follows: using PVC resin as the matrix and isocyanate as the cross-linking foaming component, relying on the reaction of isocyanate with environmental moisture and residual moisture in the formula to simultaneously complete molecular chain cross-linking and bubble formation.
[0004] Chinese patent CN116199990A discloses a high-density rigid cross-linked polyvinyl chloride (PVC) foam, whose raw materials include 500-650 parts of PVC, 10-50 parts of foaming agent, 255-450 parts of isocyanate, 5-50 parts of curing agent, 1-10 parts of surfactant, and 1-30 parts of heat stabilizer. While this process can improve foam strength, the excessive isocyanate content results in a large amount of unreacted reactive isocyanate groups remaining in the system. During long-term service in marine environments, these residual -NCO groups will continuously undergo secondary hydrolysis reactions with seawater and moisture in humid air, leading not only to deterioration of the foam's internal structure but also to uncontrolled secondary foaming. This causes fluctuations in material density, a decrease in closed-cell rate, and consequently, a gradual decline in compressive and shear strength, resulting in a significant reduction in buoyancy capacity.
[0005] Therefore, in view of the problems of PVC molecular chain rigidity, strong intermolecular forces, poor impact resistance when the material is not toughened, easy to crack, chip, delamination and breakage when subjected to stress during marine operations, and poor salt spray resistance, we continue to explore a new type of polyvinyl chloride foam material for marine operations. Summary of the Invention
[0006] The purpose of this invention is to provide a polyvinyl chloride foam material for marine operations, wherein the polyvinyl chloride foam material has excellent salt spray resistance and impact resistance.
[0007] The polyvinyl chloride foam material for marine operations described in this invention is composed of the following raw materials in parts by weight: 100 parts polyvinyl chloride resin, 6-8 parts silane-modified aluminum borate nanocrystals, 16-18 parts 1-(9,10-epoxyoctadecyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol, 3.0-5.0 parts oleic acid-modified Mg-Al-Zn ternary intercalated hydrotalcite, 38-40 parts 4,4'-diphenylmethane diisocyanate, 5-7 parts 4,4'-dicyclohexylmethane diisocyanate, 8-10 parts foaming agent, 2.5-3.0 parts di-tert-butyl peroxide, 2.0-3.0 parts heat stabilizer, 3.0-5.0 parts processing aid, 0.5 parts light stabilizer, and 0.4 parts antioxidant.
[0008] The foaming agent is a mixture of azodicarbonamide, zinc oxide, and benzene-1,3-disulfonylhydrazine, wherein the mass ratio of azodicarbonamide, zinc oxide, and benzene-1,3-disulfonylhydrazine is 1.1:0.2:0.3.
[0009] The heat stabilizer is a mixture of calcium stearate, zinc stearate, pentaerythritol and stearoyl benzoylmethane, wherein the mass ratio of calcium stearate, zinc stearate, pentaerythritol and stearoyl benzoylmethane is 1.8 : 0.7 : 0.6 : 0.3.
[0010] The processing aid is a mixture of oxidized polyethylene wax and glyceryl monostearate, with a mass ratio of oxidized polyethylene wax to glyceryl monostearate of 4:3.
[0011] The light stabilizer is hindered amine light stabilizer HS-944, CAS number 70624-18-9.
[0012] The antioxidant is a mixture of antioxidant 1010 and antioxidant 168, with a mass ratio of antioxidant 1010 to antioxidant 168 of 1:1.
[0013] The preparation method of 1-(9,10-epoxyoctadecanoyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol comprises the following steps: 9,10-epoxyoctadecanoic acid and toluene are added to a reaction apparatus, heated to 75-77°C and stirred until dissolved, then nitrogen is purged into the reaction apparatus for 30-35 minutes to replace the air inside the apparatus, hydroquinone monomethyl ether is added under nitrogen protection, the temperature is raised to 105-110°C, a mixture of triphenylphosphine-glycidyl methacrylate is added dropwise to the reaction system, and after the addition is complete, the mixture is stirred at a constant temperature of 105-110°C for 5.5 hours, heating is stopped, and the mixture is naturally cooled to 35°C under nitrogen protection. After post-treatment, 1-(9,10-epoxyoctadecanoyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol is obtained.
[0014] Of which, toluene accounts for 50% of the mass of 9,10-epoxyoctadecanoic acid.
[0015] The nitrogen flow rate is 0.5 L / min, and the entire reaction and cooling process is carried out under nitrogen protection.
[0016] Hydroquinone monomethyl ether accounts for 0.06% of the mass of glycidyl methacrylate.
[0017] The addition time of the triphenylphosphine-glycidyl methacrylate mixture is 50-60 min. The triphenylphosphine-glycidyl methacrylate mixture is obtained by dissolving triphenylphosphine in glycidyl methacrylate and mixing it evenly. The mass of triphenylphosphine accounts for 0.4% of the total mass of 9,10-epoxyoctadecanoic acid and glycidyl methacrylate, and the molar ratio of 9,10-epoxyoctadecanoic acid to glycidyl methacrylate is 1:1.13.
[0018] The post-treatment involves diluting the crude product with toluene until the total mass of toluene is 1.5 times the mass of the crude product. Insoluble matter is removed by filtration using a Buchner funnel. The filtrate is transferred to a separatory funnel, and a saturated NaHCO3 aqueous solution is added. The mixture is washed three times, with shaking for 10 seconds each time, followed by standing for 2 minutes to separate the layers. The volume of saturated NaHCO3 used in each wash is equal to the volume of the organic phase. After each shaking, the mixture is allowed to stand and separate the layers. The lower aqueous phase is removed, and the upper organic phase is retained. The upper organic phase is transferred to a clean separatory funnel, and a saturated NaCl aqueous solution is added. The volume of saturated NaCl aqueous solution used in each wash is equal to the volume of the organic phase. The mixture was washed once by shaking, allowed to stand and separate into layers, the lower aqueous phase was removed, and the upper organic phase was retained. The upper organic phase was transferred to an Erlenmeyer flask, and anhydrous Na2SO4 (8% of the organic phase mass) was added and stirred. The mixture was dried at room temperature for 3 hours, filtered through a Buchner funnel to remove the Na2SO4 solid, and the organic phase filtrate was collected. The dried organic phase filtrate was then distilled under reduced pressure at a vacuum of -0.09 MPa, a temperature of 60 °C, and a time of 2 hours to prepare 1-(9,10-epoxyoctadecanoyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol.
[0019] The structural formula of the 1-(9,10-epoxyoctadecanoyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol is as follows: .
[0020] The preparation method of oleic acid modified Mg-Al-Zn ternary intercalated hydrotalcite consists of the following steps: ① Add borax solution and deionized water to a reaction vessel and mix well. Heat to 58-62℃, and simultaneously add a mixed salt solution and sodium hydroxide solution dropwise while stirring, maintaining the pH of the system at 10.0. After the addition is complete, heat the reaction system to 65℃ and continue stirring at a constant temperature of 65℃ for 2 hours. Then allow it to stand for 12 hours for aging. Filter, wash with deionized water until the pH of the filtrate is 7.0, vacuum dry, grind through a 200-mesh sieve, and obtain tetrahydroxyborate intercalated Mg-Al-Zn. ② Tetrahydroxyborate-intercalated Mg-Al-Zn ternary hydrotalcite was added to anhydrous ethanol for ultrasonic dispersion, then heated to 65-70℃. Dilute hydrochloric acid was added dropwise to the dispersion to adjust the pH of the system to 5.5-6.0. Oleic acid-ethanol solution was added dropwise while stirring. After the addition was complete, the mixture was stirred at 65-70℃ for 2.5 h. After the reaction was completed, the mixture was filtered. The filter cake was washed twice with anhydrous ethanol, then once with deionized water, and then once with anhydrous ethanol. The filter cake was vacuum dried, pulverized and sieved to prepare oleic acid-modified Mg-Al-Zn ternary intercalated hydrotalcite.
[0021] Wherein: the borax solution mentioned in step ① is an aqueous solution with a concentration of 0.25 mol / L prepared by dissolving Na2B4O7·10H2O in deionized water.
[0022] In step ①, the mass ratio of borax solution to deionized water is 1:19-21.
[0023] In step ①, the stirring speed is 600 r / min.
[0024] The mixed salt solution mentioned in step ① is prepared by dissolving Mg(NO3)2, Al(NO3)3, and Zn(NO3)2 in deionized water, with the three components arranged in the order of Mg(NO3)2, Al(NO3)3, and Zn(NO3)2. 2+ Al 3+ Zn 2+ The molar ratio of the added metals was 3:1:0.5, and the total concentration of metal ions in the mixed salt solution was 1.0 mol / L.
[0025] In step ①, the concentration of the sodium hydroxide solution is 1.0 mol / L.
[0026] During step ①, the pH value of the reaction system is monitored in real time during the dropwise addition process. The pH value of the system is maintained at 10.0 by adding 1.0 mol / L sodium hydroxide solution.
[0027] In step ①, the vacuum drying temperature is 60℃ and the vacuum drying time is 12h.
[0028] In step ②, the mass ratio of tetrahydroxyborate-intercalated Mg-Al-Zn ternary hydrotalcite to anhydrous ethanol is 1:5-8.
[0029] In step ②, the concentration of dilute hydrochloric acid is 0.1 mol / L.
[0030] In step ②, the mass ratio of tetrahydroxyborate-intercalated Mg-Al-Zn ternary hydrotalcite to oleic acid is 1:0.1-0.12.
[0031] In step ②, the mass ratio of oleic acid to anhydrous ethanol in the oleic acid-ethanol solution is 1:4.
[0032] In step ②, the ultrasonic dispersion power is 300W, the ultrasonic dispersion time is 5-10min, and the stirring speed is 800r / min.
[0033] In step ②, the oleic acid-ethanol solution is added dropwise over a period of 20-25 minutes.
[0034] In step ②, the vacuum drying temperature is 70℃ and the vacuum drying time is 8h. After air jet pulverization, the product is passed through a 600-mesh sieve.
[0035] The preparation method of silane-modified aluminum borate nanocrystals consists of the following steps: (i) Aluminum borate nanocrystals are vacuum dried at 120℃ for 4h to obtain dried whiskers; (ii) Anhydrous ethanol and water are mixed, glacial acetic acid is added to adjust the pH of the system to 4.7, KH-550 silane coupling agent is added, and the mixture is stirred and hydrolyzed at 25℃ for 30min to obtain a hydrolysate; (iii) The dried whiskers obtained in step (i) are added to the hydrolysate, and the mixture is stirred and reacted at 67℃ for 2.5h. Then the reaction solution is pulsed and sonicated, and finally vacuum filtered, washed 3 times with anhydrous ethanol, vacuum dried at 85℃ for 3h, and pulverized through a 600-mesh sieve to obtain silane-modified aluminum borate nanocrystals.
[0036] In step (ii), the volume ratio of anhydrous ethanol to water is 92:8, and the mass of KH-550 silane coupling agent accounts for 2.5% of the mass of the dried whiskers prepared in step (i).
[0037] In step (iii), the power of the pulse ultrasound is 400W, it works for 2 seconds and stops for 1 second, and the ultrasound time is 15 minutes.
[0038] The entire process of step (ii) hydrolysis and step (iii) constant temperature stirring reaction was carried out under continuous protection of a high-purity nitrogen atmosphere.
[0039] The method for preparing polyvinyl chloride foam material for marine operations according to the present invention comprises the following steps: (1) Polyvinyl chloride resin, silane-modified aluminum borate nanocrystals, oleic acid-modified Mg-Al-Zn ternary intercalated hydrotalcite, heat stabilizer, processing aid, light stabilizer and antioxidant are added to a high-speed mixer and mixed. The mixture is cooled to 60-65℃ and 1-(9,10-epoxyoctadecyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol is added and mixed. The mixture is then cooled to 45-50℃ and foaming agent and di-tert-butyl peroxide are added and mixed. Finally, the mixture is cooled to 35-40℃ and 4,4'-diphenylmethane diisocyanate and 4,4'-dicyclohexylmethane diisocyanate are added and mixed. The mixture is then discharged to obtain the mixture. (2) Place the mixture in a mold, pressurize it to 15MPa, keep it at a constant temperature of 168-172℃ for 18-20min, and open the mold after cooling to prepare a pre-foamed blank; (3) Place the pre-foamed blank in a saturated steam treatment vessel, pre-evacuate to -0.05MPa and maintain for 8min, then introduce saturated steam to the gauge pressure of 0.05MPa, treat at 110-112℃ for 20min, then cool down to 60℃ at a rate of 3℃ / min, and release the pressure from the vessel. (4) The steam-treated foam blank is placed in a constant temperature curing oven at 75-80℃ for curing, and then slowly cooled to room temperature at a rate of 3℃ / h to prepare polyvinyl chloride foam material for marine operations.
[0040] In step (1), polyvinyl chloride resin, silane-modified aluminum borate nanocrystals, oleic acid-modified Mg-Al-Zn ternary intercalated hydrotalcite, heat stabilizer, processing aid, light stabilizer and antioxidant are added to a high-speed mixer and stirred at 96-100℃ and 1100r / min for 8-12 minutes. The mixture is then cooled to 60-65℃, and 1-(9,10-epoxyoctadecyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol is added and stirred for 3-5 minutes. The mixture is then cooled to 45-50℃, and foaming agent and di-tert-butyl peroxide are added and stirred for 2-3 minutes. Finally, the mixture is cooled to 35-40℃, and 4,4'-diphenylmethane diisocyanate and 4,4'-dicyclohexylmethane diisocyanate are added and stirred for 2 minutes. The mixture is then discharged to obtain the final product.
[0041] The mold body to be opened after cooling in step (2) is to be cooled to 60°C at a rate of 3°C / min before opening the mold.
[0042] The maturation time in step (4) is 72 hours.
[0043] Compared with the prior art, the present invention has the following advantages: (1) The polyvinyl chloride foam material for marine operations described in this invention uses polyvinyl chloride resin as the matrix resin, and silane-modified aluminum borate nanocrystals, 1-(9,10-epoxyoctadecyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol, and oleic acid-modified Mg-Al-Zn ternary intercalated hydrotalcite as modifying raw materials. 4,4'-diphenylmethane diisocyanate and 4,4'-dicyclohexylmethane diisocyanate are compounded to construct a soft-hard synergistic crosslinking network, improving the overall strength of the foam. Azodicarbonamide, benzene-1,3-disulfonylhydrazine, and zinc oxide are compounded as foaming agents to achieve gradient nucleation foaming, resulting in a high-closed-cell, low-water-absorption foam. Heat stabilizers, light stabilizers, and antioxidants synergistically inhibit damp heat and UV aging, ensuring long-term stability during marine service. Thus, the synergistic effect between the raw materials gives the prepared polyvinyl chloride foam material for marine operations excellent salt spray resistance and impact resistance.
[0044] (2) The polyvinyl chloride foam material for marine operations described in this invention, firstly, in terms of interfacial compatibility, the primary amines on the surface of the modified whiskers can form dense, multi-layered intermolecular hydrogen bonds with the β-secondary hydroxyl groups of 1-(9,10-epoxyoctadecyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol and the hydroxyl groups on the surface of oleic acid-modified Mg-Al-Zn ternary hydrotalcite. This hydrogen bond network significantly enhances the interfacial compatibility between the filler and the resin matrix, effectively reduces interfacial tension, and inhibits the tendency of filler agglomeration, thereby ensuring the integrity of the foam closed-cell structure and ensuring that the material has low water absorption and stable buoyancy performance. Secondly, in terms of mechanical toughness, the silane-modified aluminum borate nanocrystals are interwoven in the matrix, constructing a three-dimensional interwoven network. When the material is subjected to external impact, this network triggers a triple energy dissipation mechanism: first, a crack bridging effect, which locks in and prevents microcrack propagation; second, a whisker pull-out effect, which dissipates fracture energy through interfacial friction; and third, a stress deflection effect, which induces plastic deformation of the matrix and generates microcrack branches. This mechanism, synergistically with the toughening effect of 1-(9,10-epoxyoctadecanoyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol, simultaneously improves the impact resistance of the foam material at room temperature and its resistance to brittle fracture at low temperatures. Finally, in terms of salt spray resistance, the staggered silane-modified aluminum borate nanocrystals embedded in the cell walls construct a labyrinthine barrier channel, significantly extending the penetration path of chloride ions and water vapor in seawater. Meanwhile, the residual silanol and amino groups on the surface of silane-modified aluminum borate nanocrystals can assist in the adsorption of free chloride ions through coordination, forming a dual protection system with the anion exchange chloride-locking mechanism of oleic acid-modified Mg-Al-Zn ternary intercalated layered double hydroxide. This combination of physical barrier and chemical capture significantly improves the long-term service stability of foam materials in marine salt spray erosion and alternating wet and dry environments.
[0045] (3) The polyvinyl chloride foam material for marine operations described in this invention comprises an oleic acid-modified Mg-Al-Zn ternary intercalated hydrotalcite, in which magnesium, aluminum, and zinc nitrates co-precipitate in a constant weakly alkaline environment at pH=10 to form a positively charged layered hydroxide framework; the tetrahydroxyborate anion in the system is embedded in the interlayer channel during the layer growth process, and the positive charge of the layer is balanced by electrostatic attraction, and after aging and crystallization, tetrahydroxyborate intercalated Mg-Al-Zn ternary hydrotalcite is obtained. The surface of the hydrotalcite powder is rich in hydrophilic hydroxyl groups, and the carboxyl groups of the oleic acid molecules can combine with the above hydroxyl groups through hydrogen bonding, coordination or surface esterification reaction, grafting oleic acid molecules with long alkyl chains and carbon-carbon double bonds onto the outer surface of the particles. Since the size of the oleic acid molecule is larger than the height of the interlayer channel of the hydrotalcite, the modification process mainly occurs on the outer surface, and the interlayer is used to capture Cl. -The tetrahydroxyborate ions were largely undisplaced and effectively retained. After modification, the powder changed from hydrophilic to lipophilic, allowing it to be uniformly dispersed in the PVC foam matrix. Simultaneously, during the PVC hot mixing process, the carbon-carbon double bonds in the oleic acid molecules could graft or crosslink with the PVC molecular chains, forming a weak interfacial bonding network, thereby helping to improve the toughness and impact resistance of the foam material.
[0046] (4) The polyvinyl chloride foam material for marine operations described in this invention, wherein the 1-(9,10-epoxyoctadecanoyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol utilizes triphenylphosphine as a nucleophilic catalyst to attack the epoxy carbon atom of glycidyl methacrylate, forming a phosphonium-alkoxide zwitterionic intermediate. Subsequently, this intermediate is subjected to nucleophilic attack by the oxygen atom in the carboxyl group of 9,10-epoxyoctadecanoic acid, undergoing a ring-opening esterification reaction via proton transfer. This reaction successfully grafts polymerizable methacryloyloxy onto long-chain fatty acid molecules, while introducing β-hydroxyl groups into the molecular chain, enhancing adhesion to polar substrates. During the reaction, the aliphatic epoxy groups of 9,10-epoxyoctadecanoic acid itself, due to their large steric hindrance and weak electrophilicity, do not participate in the reaction under these reaction conditions, thus remaining in the final product structure, giving the product multiple reactive sites such as acrylate double bonds, β-hydroxyl groups, and epoxy groups.
[0047] (5) The preparation method of the polyvinyl chloride foam material for marine operations described in this invention is simple, the parameters are easy to control, and the polyvinyl chloride foam material prepared has stable performance. Detailed Implementation
[0048] Example 1
[0049] The polyvinyl chloride foam material for marine operations described in Example 1 is composed of the following raw materials by weight: 100 parts polyvinyl chloride resin, 7 parts silane-modified aluminum borate nanocrystals, 17 parts 1-(9,10-epoxyoctadecyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol, 4 parts oleic acid-modified Mg-Al-Zn ternary intercalated hydrotalcite, 39 parts 4,4'-diphenylmethane diisocyanate, 6 parts 4,4'-dicyclohexylmethane diisocyanate, 9 parts foaming agent, 2.7 parts di-tert-butyl peroxide, 2.5 parts heat stabilizer, 4 parts processing aid, 0.5 parts light stabilizer, and 0.4 parts antioxidant.
[0050] The foaming agent is a mixture of azodicarbonamide, zinc oxide, and benzene-1,3-disulfonylhydrazine, wherein the mass ratio of azodicarbonamide, zinc oxide, and benzene-1,3-disulfonylhydrazine is 1.1:0.2:0.3.
[0051] The heat stabilizer is a mixture of calcium stearate, zinc stearate, pentaerythritol and stearoyl benzoylmethane, wherein the mass ratio of calcium stearate, zinc stearate, pentaerythritol and stearoyl benzoylmethane is 1.8 : 0.7 : 0.6 : 0.3.
[0052] The processing aid is a mixture of oxidized polyethylene wax and glyceryl monostearate, with a mass ratio of oxidized polyethylene wax to glyceryl monostearate of 4:3.
[0053] The light stabilizer is hindered amine light stabilizer HS-944, CAS number 70624-18-9.
[0054] The antioxidant is a mixture of antioxidant 1010 and antioxidant 168, with a mass ratio of antioxidant 1010 to antioxidant 168 of 1:1.
[0055] The preparation method of 1-(9,10-epoxyoctadecanoyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol comprises the following steps: 9,10-epoxyoctadecanoic acid and toluene are added to a reaction apparatus, heated to 76°C and stirred until dissolved, then nitrogen is purged into the reaction apparatus for 33 minutes to replace the air inside the apparatus, hydroquinone monomethyl ether is added under nitrogen protection, the temperature is raised to 107°C, a mixture of triphenylphosphine-glycidyl methacrylate is added dropwise to the reaction system, after the addition is complete, the mixture is stirred at a constant temperature of 107°C for 5.5 hours, heating is stopped, and the mixture is naturally cooled to 35°C under nitrogen protection. After post-treatment, 1-(9,10-epoxyoctadecanoyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol is obtained.
[0056] Of which, toluene accounts for 50% of the mass of 9,10-epoxyoctadecanoic acid.
[0057] The nitrogen flow rate is 0.5 L / min, and the entire reaction and cooling process is carried out under nitrogen protection.
[0058] Hydroquinone monomethyl ether accounts for 0.06% of the mass of glycidyl methacrylate.
[0059] The triphenylphosphine-glycidyl methacrylate mixture was added over a period of 55 minutes. The triphenylphosphine-glycidyl methacrylate mixture was obtained by dissolving triphenylphosphine in glycidyl methacrylate and mixing thoroughly. The mass of triphenylphosphine accounted for 0.4% of the total mass of 9,10-epoxyoctadecanoic acid and glycidyl methacrylate, and the molar ratio of 9,10-epoxyoctadecanoic acid to glycidyl methacrylate was 1:1.13.
[0060] The post-treatment involves diluting the crude product with toluene until the total mass of toluene is 1.5 times the mass of the crude product. Insoluble matter is removed by filtration using a Buchner funnel. The filtrate is transferred to a separatory funnel, and a saturated NaHCO3 aqueous solution is added. The mixture is washed three times, with shaking for 10 seconds each time, followed by standing for 2 minutes to separate the layers. The volume of saturated NaHCO3 used in each wash is equal to the volume of the organic phase. After each shaking, the mixture is allowed to stand and separate the layers. The lower aqueous phase is removed, and the upper organic phase is retained. The upper organic phase is transferred to a clean separatory funnel, and a saturated NaCl aqueous solution is added. The volume of saturated NaCl aqueous solution used in each wash is equal to the volume of the organic phase. The mixture was washed once by shaking, allowed to stand and separate into layers, the lower aqueous phase was removed, and the upper organic phase was retained. The upper organic phase was transferred to an Erlenmeyer flask, and anhydrous Na2SO4 (8% of the organic phase mass) was added and stirred. The mixture was dried at room temperature for 3 hours, filtered through a Buchner funnel to remove the Na2SO4 solid, and the organic phase filtrate was collected. The dried organic phase filtrate was then distilled under reduced pressure at a vacuum of -0.09 MPa, a temperature of 60 °C, and a time of 2 hours to prepare 1-(9,10-epoxyoctadecanoyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol.
[0061] The structural formula of the 1-(9,10-epoxyoctadecanoyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol is as follows: .
[0062] The preparation method of oleic acid modified Mg-Al-Zn ternary intercalated hydrotalcite consists of the following steps: ① Add borax solution and deionized water to a reaction vessel and mix well. Heat to 60℃, and simultaneously add a mixed salt solution and sodium hydroxide solution dropwise while stirring, maintaining the pH of the system at 10.0. After the addition is complete, heat the reaction system to 65℃ and continue stirring at a constant temperature of 65℃ for 2 hours. Then let it stand for 12 hours for aging. Filter, wash with deionized water until the pH of the filtrate is 7.0, vacuum dry, grind through a 200-mesh sieve, and obtain tetrahydroxyborate intercalated Mg-Al ① Oleic acid-modified Mg-Al-Zn ternary hydrotalcite; ② Tetrahydroxyborate-intercalated Mg-Al-Zn ternary hydrotalcite was added to anhydrous ethanol for ultrasonic dispersion, then heated to 67℃, and dilute hydrochloric acid was added dropwise to adjust the pH of the system to 5.7. Oleic acid-ethanol solution was added dropwise while stirring. After the addition was complete, the mixture was stirred at 67℃ for 2.5 h. After the reaction was completed, the mixture was filtered. The filter cake was washed twice with anhydrous ethanol, then once with deionized water, and then once with anhydrous ethanol. The filter cake was vacuum dried, pulverized and sieved to prepare oleic acid-modified Mg-Al-Zn ternary intercalated hydrotalcite.
[0063] Wherein: the borax solution mentioned in step ① is an aqueous solution with a concentration of 0.25 mol / L prepared by dissolving Na2B4O7·10H2O in deionized water.
[0064] In step ①, the mass ratio of borax solution to deionized water is 1:20.
[0065] In step ①, the stirring speed is 600 r / min.
[0066] The mixed salt solution mentioned in step ① is prepared by dissolving Mg(NO3)2, Al(NO3)3, and Zn(NO3)2 in deionized water, with the three components arranged in the order of Mg(NO3)2, Al(NO3)3, and Zn(NO3)2. 2+ Al 3+ Zn 2+ The molar ratio of the added metals was 3:1:0.5, and the total concentration of metal ions in the mixed salt solution was 1.0 mol / L.
[0067] In step ①, the concentration of the sodium hydroxide solution is 1.0 mol / L.
[0068] During step ①, the pH value of the reaction system is monitored in real time during the dropwise addition process. The pH value of the system is maintained at 10.0 by adding 1.0 mol / L sodium hydroxide solution.
[0069] In step ①, the vacuum drying temperature is 60℃ and the vacuum drying time is 12h.
[0070] In step ②, the mass ratio of tetrahydroxyborate-intercalated Mg-Al-Zn ternary hydrotalcite to anhydrous ethanol is 1:6.5.
[0071] In step ②, the concentration of dilute hydrochloric acid is 0.1 mol / L.
[0072] In step ②, the mass ratio of tetrahydroxyborate-intercalated Mg-Al-Zn ternary hydrotalcite to oleic acid is 1:0.11.
[0073] In step ②, the mass ratio of oleic acid to anhydrous ethanol in the oleic acid-ethanol solution is 1:4.
[0074] In step ②, the ultrasonic dispersion power is 300W, the ultrasonic dispersion time is 7min, and the stirring speed is 800r / min.
[0075] In step ②, the oleic acid-ethanol solution is added over a period of 23 minutes.
[0076] In step ②, the vacuum drying temperature is 70℃ and the vacuum drying time is 8h. After air jet pulverization, the product is passed through a 600-mesh sieve.
[0077] The preparation method of silane-modified aluminum borate nanocrystals consists of the following steps: (i) Aluminum borate nanocrystals are vacuum dried at 120℃ for 4h to obtain dried whiskers; (ii) Anhydrous ethanol and water are mixed, glacial acetic acid is added to adjust the pH of the system to 4.7, KH-550 silane coupling agent is added, and the mixture is stirred and hydrolyzed at 25℃ for 30min to obtain a hydrolysate; (iii) The dried whiskers obtained in step (i) are added to the hydrolysate, and the mixture is stirred and reacted at 67℃ for 2.5h. Then the reaction solution is pulsed and sonicated, and finally vacuum filtered, washed 3 times with anhydrous ethanol, vacuum dried at 85℃ for 3h, and pulverized through a 600-mesh sieve to obtain silane-modified aluminum borate nanocrystals.
[0078] In step (ii), the volume ratio of anhydrous ethanol to water is 92:8, and the mass of KH-550 silane coupling agent accounts for 2.5% of the mass of the dried whiskers prepared in step (i).
[0079] In step (3), the pulsed ultrasound power is 400W, the operation lasts 2 seconds and stops for 1 second, and the ultrasound time is 15 minutes.
[0080] The entire process of step (ii) hydrolysis and step (iii) constant temperature stirring reaction was carried out under continuous protection of a high-purity nitrogen atmosphere.
[0081] The preparation method of the polyvinyl chloride foam material for marine operations described in Example 1 consists of the following steps: (1) Polyvinyl chloride resin, silane-modified aluminum borate nanocrystals, oleic acid-modified Mg-Al-Zn ternary intercalated hydrotalcite, heat stabilizer, processing aid, light stabilizer and antioxidant are added to a high-speed mixer and mixed. The mixture is cooled to 63°C and 1-(9,10-epoxyoctadecyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol is added and mixed. The mixture is then cooled to 47°C and foaming agent and di-tert-butyl peroxide are added and mixed. Finally, the mixture is cooled to 37°C and 4,4'-diphenylmethane diisocyanate and 4,4'-dicyclohexylmethane diisocyanate are added and mixed. The mixture is then discharged to obtain the mixture. (2) Place the mixture in a mold, pressurize it to 15MPa, keep it at a constant temperature of 168-172℃ for 18-20min, and open the mold after cooling to prepare a pre-foamed blank; (3) Place the pre-foamed blank in a saturated steam treatment vessel, pre-evacuate to -0.05MPa and maintain for 8min, then introduce saturated steam to the gauge pressure of 0.05MPa, treat at 111℃ for 20min, then cool down to 60℃ at a rate of 3℃ / min, and release the pressure from the vessel. (4) The steam-treated foam blank is placed in a constant temperature curing oven at 77°C for curing, and then slowly cooled to room temperature at a rate of 3°C / h to prepare polyvinyl chloride foam material for marine operations.
[0082] In step (1), polyvinyl chloride resin, silane-modified aluminum borate nanocrystals, oleic acid-modified Mg-Al-Zn ternary intercalated hydrotalcite, heat stabilizer, processing aid, light stabilizer and antioxidant are added to a high-speed mixer and stirred at 98℃ and 1100r / min for 10min. The mixture is then cooled to 63℃, and 1-(9,10-epoxyoctadecyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol is added and stirred for 4min. The mixture is then cooled to 47℃, and foaming agent and di-tert-butyl peroxide are added and stirred for 2min. Finally, the mixture is cooled to 37℃, and 4,4'-diphenylmethane diisocyanate and 4,4'-dicyclohexylmethane diisocyanate are added and stirred for 2min. The mixture is then discharged to obtain the final product.
[0083] The mold body to be opened after cooling in step (2) is to be cooled to 60°C at a rate of 3°C / min before opening the mold.
[0084] The maturation time in step (4) is 72 hours.
[0085] Example 2
[0086] The polyvinyl chloride foam material for marine operations described in Example 2 is composed of the following raw materials by weight: 100 parts polyvinyl chloride resin, 6 parts silane-modified aluminum borate nanocrystals, 16 parts 1-(9,10-epoxyoctadecyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol, 5.0 parts oleic acid-modified Mg-Al-Zn ternary intercalated hydrotalcite, 38 parts 4,4'-diphenylmethane diisocyanate, 7 parts 4,4'-dicyclohexylmethane diisocyanate, 10 parts foaming agent, 2.5 parts di-tert-butyl peroxide, 2.0 parts heat stabilizer, 3.0 parts processing aid, 0.5 parts light stabilizer, and 0.4 parts antioxidant.
[0087] The foaming agent is a mixture of azodicarbonamide, zinc oxide, and benzene-1,3-disulfonylhydrazine, wherein the mass ratio of azodicarbonamide, zinc oxide, and benzene-1,3-disulfonylhydrazine is 1.1:0.2:0.3.
[0088] The heat stabilizer is a mixture of calcium stearate, zinc stearate, pentaerythritol and stearoyl benzoylmethane, wherein the mass ratio of calcium stearate, zinc stearate, pentaerythritol and stearoyl benzoylmethane is 1.8 : 0.7 : 0.6 : 0.3.
[0089] The processing aid is a mixture of oxidized polyethylene wax and glyceryl monostearate, with a mass ratio of oxidized polyethylene wax to glyceryl monostearate of 4:3.
[0090] The light stabilizer is hindered amine light stabilizer HS-944, CAS number 70624-18-9.
[0091] The antioxidant is a mixture of antioxidant 1010 and antioxidant 168, with a mass ratio of antioxidant 1010 to antioxidant 168 of 1:1.
[0092] The preparation method of 1-(9,10-epoxyoctadecanoyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol comprises the following steps: 9,10-epoxyoctadecanoic acid and toluene are added to a reaction apparatus, heated to 75°C and stirred until dissolved, then nitrogen is purged into the reaction apparatus for 30 minutes to replace the air inside the apparatus, hydroquinone monomethyl ether is added under nitrogen protection, the temperature is raised to 105°C, a mixture of triphenylphosphine-glycidyl methacrylate is added dropwise to the reaction system, after the addition is complete, the mixture is stirred at a constant temperature of 105°C for 5.5 hours, heating is stopped, and the mixture is naturally cooled to 35°C under nitrogen protection. After post-treatment, 1-(9,10-epoxyoctadecanoyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol is obtained.
[0093] Of which, toluene accounts for 50% of the mass of 9,10-epoxyoctadecanoic acid.
[0094] The nitrogen flow rate is 0.5 L / min, and the entire reaction and cooling process is carried out under nitrogen protection.
[0095] Hydroquinone monomethyl ether accounts for 0.06% of the mass of glycidyl methacrylate.
[0096] The triphenylphosphine-glycidyl methacrylate mixture was added over a period of 50 minutes. The triphenylphosphine-glycidyl methacrylate mixture was obtained by dissolving triphenylphosphine in glycidyl methacrylate and mixing thoroughly. The mass of triphenylphosphine accounted for 0.4% of the total mass of 9,10-epoxyoctadecanoic acid and glycidyl methacrylate, and the molar ratio of 9,10-epoxyoctadecanoic acid to glycidyl methacrylate was 1:1.13.
[0097] The post-treatment involves diluting the crude product with toluene until the total mass of toluene is 1.5 times the mass of the crude product. Insoluble matter is removed by filtration using a Buchner funnel. The filtrate is transferred to a separatory funnel, and a saturated NaHCO3 aqueous solution is added. The mixture is washed three times, with shaking for 10 seconds each time, followed by standing for 2 minutes to separate the layers. The volume of saturated NaHCO3 used in each wash is equal to the volume of the organic phase. After each shaking, the mixture is allowed to stand and separate the layers. The lower aqueous phase is removed, and the upper organic phase is retained. The upper organic phase is transferred to a clean separatory funnel, and a saturated NaCl aqueous solution is added. The volume of saturated NaCl aqueous solution used in each wash is equal to the volume of the organic phase. The mixture was washed once by shaking, allowed to stand and separate into layers, the lower aqueous phase was removed, and the upper organic phase was retained. The upper organic phase was transferred to an Erlenmeyer flask, and anhydrous Na2SO4 (8% of the organic phase mass) was added and stirred. The mixture was dried at room temperature for 3 hours, filtered through a Buchner funnel to remove the Na2SO4 solid, and the organic phase filtrate was collected. The dried organic phase filtrate was then distilled under reduced pressure at a vacuum of -0.09 MPa, a temperature of 60 °C, and a time of 2 hours to prepare 1-(9,10-epoxyoctadecanoyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol.
[0098] The structural formula of the 1-(9,10-epoxyoctadecanoyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol is as follows: .
[0099] The preparation method of oleic acid modified Mg-Al-Zn ternary intercalated hydrotalcite consists of the following steps: ① Add borax solution and deionized water to a reaction vessel and mix well. Heat to 62℃, and simultaneously add a mixed salt solution and sodium hydroxide solution dropwise while stirring, maintaining the pH of the system at 10.0. After the addition is complete, heat the reaction system to 65℃ and continue stirring at a constant temperature of 65℃ for 2 hours. Then let it stand for 12 hours for aging. Filter, wash with deionized water until the pH of the filtrate is 7.0, vacuum dry, grind through a 200-mesh sieve, and obtain tetrahydroxyborate intercalated Mg-Al ① Oleic acid-modified Mg-Al-Zn ternary hydrotalcite; ② Tetrahydroxyborate-intercalated Mg-Al-Zn ternary hydrotalcite was added to anhydrous ethanol for ultrasonic dispersion, then heated to 70℃, and dilute hydrochloric acid was added dropwise to adjust the pH of the system to 6.0. Oleic acid-ethanol solution was added dropwise while stirring. After the addition was complete, the mixture was stirred at 70℃ for 2.5 h. After the reaction was completed, the mixture was filtered. The filter cake was washed twice with anhydrous ethanol, then once with deionized water, and then once with anhydrous ethanol. The filter cake was vacuum dried, pulverized and sieved to prepare oleic acid-modified Mg-Al-Zn ternary intercalated hydrotalcite.
[0100] Wherein: the borax solution mentioned in step ① is an aqueous solution with a concentration of 0.25 mol / L prepared by dissolving Na2B4O7·10H2O in deionized water.
[0101] In step ①, the mass ratio of borax solution to deionized water is 1:19.
[0102] In step ①, the stirring speed is 600 r / min.
[0103] The mixed salt solution mentioned in step ① is prepared by dissolving Mg(NO3)2, Al(NO3)3, and Zn(NO3)2 in deionized water, with the three components arranged in the order of Mg(NO3)2, Al(NO3)3, and Zn(NO3)2. 2+ Al 3+ Zn 2+ The molar ratio of the added metals was 3:1:0.5, and the total concentration of metal ions in the mixed salt solution was 1.0 mol / L.
[0104] In step ①, the concentration of the sodium hydroxide solution is 1.0 mol / L.
[0105] During step ①, the pH value of the reaction system is monitored in real time during the dropwise addition process. The pH value of the system is maintained at 10.0 by adding 1.0 mol / L sodium hydroxide solution.
[0106] In step ①, the vacuum drying temperature is 60℃ and the vacuum drying time is 12h.
[0107] In step ②, the mass ratio of tetrahydroxyborate-intercalated Mg-Al-Zn ternary hydrotalcite to anhydrous ethanol is 1:5.
[0108] In step ②, the concentration of dilute hydrochloric acid is 0.1 mol / L.
[0109] In step ②, the mass ratio of tetrahydroxyborate-intercalated Mg-Al-Zn ternary hydrotalcite to oleic acid is 1:0.12.
[0110] In step ②, the mass ratio of oleic acid to anhydrous ethanol in the oleic acid-ethanol solution is 1:4.
[0111] In step ②, the ultrasonic dispersion power is 300W, the ultrasonic dispersion time is 10min, and the stirring speed is 800r / min.
[0112] In step ②, the oleic acid-ethanol solution is added over a period of 25 minutes.
[0113] In step ②, the vacuum drying temperature is 70℃ and the vacuum drying time is 8h. After air jet pulverization, the product is passed through a 600-mesh sieve.
[0114] The preparation method of silane-modified aluminum borate nanocrystals consists of the following steps: (i) Aluminum borate nanocrystals are vacuum dried at 120℃ for 4h to obtain dried whiskers; (ii) Anhydrous ethanol and water are mixed, glacial acetic acid is added to adjust the pH of the system to 4.7, KH-550 silane coupling agent is added, and the mixture is stirred and hydrolyzed at 25℃ for 30min to obtain a hydrolysate; (iii) The dried whiskers obtained in step (i) are added to the hydrolysate, and the mixture is stirred and reacted at 67℃ for 2.5h. Then the reaction solution is pulsed and sonicated, and finally vacuum filtered, washed 3 times with anhydrous ethanol, vacuum dried at 85℃ for 3h, and pulverized through a 600-mesh sieve to obtain silane-modified aluminum borate nanocrystals.
[0115] In step (ii), the volume ratio of anhydrous ethanol to water is 92:8, and the mass of KH-550 silane coupling agent accounts for 2.5% of the mass of the dried whiskers prepared in step (i).
[0116] In step (iii), the power of the pulse ultrasound is 400W, it works for 2 seconds and stops for 1 second, and the ultrasound time is 15 minutes.
[0117] The entire process of step (ii) hydrolysis and step (iii) constant temperature stirring reaction was carried out under continuous protection of a high-purity nitrogen atmosphere.
[0118] The preparation method of the polyvinyl chloride foam material for marine operations described in Example 2 consists of the following steps: (1) Polyvinyl chloride resin, silane-modified aluminum borate nanocrystals, oleic acid-modified Mg-Al-Zn ternary intercalated hydrotalcite, heat stabilizer, processing aid, light stabilizer and antioxidant are added to a high-speed mixer and mixed. The mixture is cooled to 60°C and 1-(9,10-epoxyoctadecyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol is added and mixed. The mixture is then cooled to 45°C and foaming agent and di-tert-butyl peroxide are added and mixed. Finally, the mixture is cooled to 35°C and 4,4'-diphenylmethane diisocyanate and 4,4'-dicyclohexylmethane diisocyanate are added and mixed. The mixture is then discharged to obtain the mixture. (2) Place the mixture in a mold, pressurize it to 15MPa, keep it at 168℃ for 20min, and open the mold after cooling to prepare a pre-foamed blank; (3) Place the pre-foamed blank in a saturated steam treatment vessel, pre-evacuate to -0.05MPa and maintain for 8min, then introduce saturated steam to the gauge pressure of 0.05MPa, treat at 110℃ for 20min, then cool down to 60℃ at a rate of 3℃ / min, and release the pressure from the vessel. (4) The steam-treated foam blank is placed in a constant temperature curing oven at 75°C for curing, and then slowly cooled to room temperature at a rate of 3°C / h to prepare polyvinyl chloride foam material for marine operations.
[0119] In step (1), polyvinyl chloride resin, silane-modified aluminum borate nanocrystals, oleic acid-modified Mg-Al-Zn ternary intercalated hydrotalcite, heat stabilizer, processing aid, light stabilizer and antioxidant are added to a high-speed mixer and stirred at 96℃ and 1100r / min for 12min. The mixture is then cooled to 60℃, and 1-(9,10-epoxyoctadecyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol is added and stirred for 5min. The mixture is then cooled to 45℃, and foaming agent and di-tert-butyl peroxide are added and stirred for 3min. Finally, the mixture is cooled to 35℃, and 4,4'-diphenylmethane diisocyanate and 4,4'-dicyclohexylmethane diisocyanate are added and stirred for 2min. The mixture is then discharged to obtain the final product.
[0120] The mold body to be opened after cooling in step (2) is to be cooled to 60°C at a rate of 3°C / min before opening the mold.
[0121] The maturation time in step (4) is 72 hours.
[0122] Example 3
[0123] The polyvinyl chloride foam material for marine operations described in Example 3 is composed of the following raw materials by weight: 100 parts polyvinyl chloride resin, 8 parts silane-modified aluminum borate nanocrystals, 18 parts 1-(9,10-epoxyoctadecyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol, 3.0 parts oleic acid-modified Mg-Al-Zn ternary intercalated hydrotalcite, 40 parts 4,4'-diphenylmethane diisocyanate, 5 parts 4,4'-dicyclohexylmethane diisocyanate, 8 parts foaming agent, 3.0 parts di-tert-butyl peroxide, 3.0 parts heat stabilizer, 5.0 parts processing aid, 0.5 parts light stabilizer, and 0.4 parts antioxidant.
[0124] The foaming agent is a mixture of azodicarbonamide, zinc oxide, and benzene-1,3-disulfonylhydrazine, wherein the mass ratio of azodicarbonamide, zinc oxide, and benzene-1,3-disulfonylhydrazine is 1.1:0.2:0.3.
[0125] The heat stabilizer is a mixture of calcium stearate, zinc stearate, pentaerythritol and stearoyl benzoylmethane, wherein the mass ratio of calcium stearate, zinc stearate, pentaerythritol and stearoyl benzoylmethane is 1.8 : 0.7 : 0.6 : 0.3.
[0126] The processing aid is a mixture of oxidized polyethylene wax and glyceryl monostearate, with a mass ratio of oxidized polyethylene wax to glyceryl monostearate of 4:3.
[0127] The light stabilizer is hindered amine light stabilizer HS-944, CAS number 70624-18-9.
[0128] The antioxidant is a mixture of antioxidant 1010 and antioxidant 168, with a mass ratio of antioxidant 1010 to antioxidant 168 of 1:1.
[0129] The preparation method of 1-(9,10-epoxyoctadecanoyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol comprises the following steps: 9,10-epoxyoctadecanoic acid and toluene are added to a reaction apparatus, heated to 77°C and stirred until dissolved, then nitrogen is purged into the reaction apparatus for 35 minutes to replace the air inside the apparatus, hydroquinone monomethyl ether is added under nitrogen protection, the temperature is raised to 110°C, a mixture of triphenylphosphine-glycidyl methacrylate is added dropwise to the reaction system, after the addition is complete, the mixture is stirred at a constant temperature of 110°C for 5.5 hours, heating is stopped, and the mixture is naturally cooled to 35°C under nitrogen protection. After post-treatment, 1-(9,10-epoxyoctadecanoyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol is obtained.
[0130] Of which, toluene accounts for 50% of the mass of 9,10-epoxyoctadecanoic acid.
[0131] The nitrogen flow rate is 0.5 L / min, and the entire reaction and cooling process is carried out under nitrogen protection.
[0132] Hydroquinone monomethyl ether accounts for 0.06% of the mass of glycidyl methacrylate.
[0133] The triphenylphosphine-glycidyl methacrylate mixture was added over a period of 60 minutes. The triphenylphosphine-glycidyl methacrylate mixture was obtained by dissolving triphenylphosphine in glycidyl methacrylate and mixing thoroughly. The mass of triphenylphosphine accounted for 0.4% of the total mass of 9,10-epoxyoctadecanoic acid and glycidyl methacrylate, and the molar ratio of 9,10-epoxyoctadecanoic acid to glycidyl methacrylate was 1:1.13.
[0134] The post-treatment involves diluting the crude product with toluene until the total mass of toluene is 1.5 times the mass of the crude product. Insoluble matter is removed by filtration using a Buchner funnel. The filtrate is transferred to a separatory funnel, and a saturated NaHCO3 aqueous solution is added. The mixture is washed three times, with shaking for 10 seconds each time, followed by standing for 2 minutes to separate the layers. The volume of saturated NaHCO3 used in each wash is equal to the volume of the organic phase. After each shaking, the mixture is allowed to stand and separate the layers. The lower aqueous phase is removed, and the upper organic phase is retained. The upper organic phase is transferred to a clean separatory funnel, and a saturated NaCl aqueous solution is added. The volume of saturated NaCl aqueous solution used in each wash is equal to the volume of the organic phase. The mixture was washed once by shaking, allowed to stand and separate into layers, the lower aqueous phase was removed, and the upper organic phase was retained. The upper organic phase was transferred to an Erlenmeyer flask, and anhydrous Na2SO4 (8% of the organic phase mass) was added and stirred. The mixture was dried at room temperature for 3 hours, filtered through a Buchner funnel to remove the Na2SO4 solid, and the organic phase filtrate was collected. The dried organic phase filtrate was then distilled under reduced pressure at a vacuum of -0.09 MPa, a temperature of 60 °C, and a time of 2 hours to prepare 1-(9,10-epoxyoctadecanoyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol.
[0135] The structural formula of the 1-(9,10-epoxyoctadecanoyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol is as follows: .
[0136] The preparation method of oleic acid modified Mg-Al-Zn ternary intercalated hydrotalcite consists of the following steps: ① Add borax solution and deionized water to a reaction vessel and mix well. Heat to 58℃, and simultaneously add a mixed salt solution and sodium hydroxide solution dropwise while stirring, maintaining the pH of the system at 10.0. After the addition is complete, heat the reaction system to 65℃ and continue stirring at a constant temperature of 65℃ for 2 hours. Then allow it to stand and age for 12 hours, filter, wash with deionized water until the pH of the filtrate is 7.0, vacuum dry, grind through a 200-mesh sieve, and prepare tetrahydroxyborate intercalated Mg-Al-Zn hydrotalcite. ② Tetrahydroxyborate-intercalated Mg-Al-Zn ternary hydrotalcite was added to anhydrous ethanol for ultrasonic dispersion, then heated to 65℃. Dilute hydrochloric acid was added dropwise to the dispersion to adjust the pH of the system to 5.5. Oleic acid-ethanol solution was added dropwise while stirring. After the addition was complete, the mixture was stirred at 65-70℃ for 2.5 h. After the reaction was completed, the mixture was filtered. The filter cake was washed twice with anhydrous ethanol, then once with deionized water, and then once with anhydrous ethanol. The filter cake was vacuum dried, pulverized and sieved to prepare oleic acid-modified Mg-Al-Zn ternary intercalated hydrotalcite.
[0137] Wherein: the borax solution mentioned in step ① is an aqueous solution with a concentration of 0.25 mol / L prepared by dissolving Na2B4O7·10H2O in deionized water.
[0138] In step ①, the mass ratio of borax solution to deionized water is 1:21.
[0139] In step ①, the stirring speed is 600 r / min.
[0140] The mixed salt solution mentioned in step ① is prepared by dissolving Mg(NO3)2, Al(NO3)3, and Zn(NO3)2 in deionized water, with the three components arranged in the order of Mg(NO3)2, Al(NO3)3, and Zn(NO3)2. 2+ Al 3+ Zn 2+ The molar ratio of the added metals was 3:1:0.5, and the total concentration of metal ions in the mixed salt solution was 1.0 mol / L.
[0141] In step ①, the concentration of the sodium hydroxide solution is 1.0 mol / L.
[0142] During step ①, the pH value of the reaction system is monitored in real time during the dropwise addition process. The pH value of the system is maintained at 10.0 by adding 1.0 mol / L sodium hydroxide solution.
[0143] In step ①, the vacuum drying temperature is 60℃ and the vacuum drying time is 12h.
[0144] In step ②, the mass ratio of tetrahydroxyborate-intercalated Mg-Al-Zn ternary hydrotalcite to anhydrous ethanol is 1:8.
[0145] In step ②, the concentration of dilute hydrochloric acid is 0.1 mol / L.
[0146] In step ②, the mass ratio of tetrahydroxyborate-intercalated Mg-Al-Zn ternary hydrotalcite to oleic acid is 1:0.1.
[0147] In step ②, the mass ratio of oleic acid to anhydrous ethanol in the oleic acid-ethanol solution is 1:4.
[0148] In step ②, the ultrasonic dispersion power is 300W, the ultrasonic dispersion time is 5min, and the stirring speed is 800r / min.
[0149] In step ②, the oleic acid-ethanol solution is added over a period of 20 minutes.
[0150] In step ②, the vacuum drying temperature is 70℃ and the vacuum drying time is 8h. After air jet pulverization, the product is passed through a 600-mesh sieve.
[0151] The preparation method of silane-modified aluminum borate nanocrystals consists of the following steps: (i) Aluminum borate nanocrystals are vacuum dried at 120℃ for 4h to obtain dried whiskers; (ii) Anhydrous ethanol and water are mixed, glacial acetic acid is added to adjust the pH of the system to 4.7, KH-550 silane coupling agent is added, and the mixture is stirred and hydrolyzed at 25℃ for 30min to obtain a hydrolysate; (iii) The dried whiskers obtained in step (i) are added to the hydrolysate, and the mixture is stirred and reacted at 67℃ for 2.5h. Then the reaction solution is pulsed and sonicated, and finally vacuum filtered, washed 3 times with anhydrous ethanol, vacuum dried at 85℃ for 3h, and pulverized through a 600-mesh sieve to obtain silane-modified aluminum borate nanocrystals.
[0152] In step (ii), the volume ratio of anhydrous ethanol to water is 92:8, and the mass of KH-550 silane coupling agent accounts for 2.5% of the mass of the dried whiskers prepared in step (i).
[0153] In step (iii), the power of the pulse ultrasound is 400W, it works for 2 seconds and stops for 1 second, and the ultrasound time is 15 minutes.
[0154] The entire process of step (ii) hydrolysis and step (iii) constant temperature stirring reaction was carried out under continuous protection of a high-purity nitrogen atmosphere.
[0155] The preparation method of the polyvinyl chloride foam material for marine operations described in Example 3 consists of the following steps: (1) Polyvinyl chloride resin, silane-modified aluminum borate nanocrystals, oleic acid-modified Mg-Al-Zn ternary intercalated hydrotalcite, heat stabilizer, processing aid, light stabilizer and antioxidant are added to a high-speed mixer and mixed. The mixture is cooled to 65°C and 1-(9,10-epoxyoctadecyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol is added and mixed. The mixture is further cooled to 50°C and foaming agent and di-tert-butyl peroxide are added and mixed. Finally, the mixture is cooled to 40°C and 4,4'-diphenylmethane diisocyanate and 4,4'-dicyclohexylmethane diisocyanate are added and mixed. The mixture is then discharged to obtain the mixture. (2) Place the mixture in a mold, pressurize it to 15MPa, keep it at 172℃ for 18min, and open the mold after cooling to prepare a pre-foamed blank; (3) Place the pre-foamed blank in a saturated steam treatment vessel, pre-evacuate to -0.05MPa and maintain for 8min, then introduce saturated steam to the gauge pressure of 0.05MPa, treat at 112℃ for 20min, then cool down to 60℃ at a rate of 3℃ / min, and release the pressure from the vessel. (4) The steam-treated foam blank is placed in a constant temperature curing oven at 80°C for curing, and then slowly cooled to room temperature at a rate of 3°C / h to prepare polyvinyl chloride foam material for marine operations.
[0156] In step (1), polyvinyl chloride resin, silane-modified aluminum borate nanocrystals, oleic acid-modified Mg-Al-Zn ternary intercalated hydrotalcite, heat stabilizer, processing aid, light stabilizer and antioxidant are added to a high-speed mixer and stirred at 100℃ and 1100r / min for 8 minutes. The mixture is then cooled to 65℃, and 1-(9,10-epoxyoctadecyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol is added and stirred for 3 minutes. The mixture is then cooled to 50℃, and foaming agent and di-tert-butyl peroxide are added and stirred for 2 minutes. Finally, the mixture is cooled to 40℃, and 4,4'-diphenylmethane diisocyanate and 4,4'-dicyclohexylmethane diisocyanate are added and stirred for 2 minutes. The mixture is then discharged to obtain the final product.
[0157] The mold body to be opened after cooling in step (2) is to be cooled to 60°C at a rate of 3°C / min before opening the mold.
[0158] The maturation time in step (4) is 72 hours.
[0159] Comparative Example 1 The preparation method of the polyvinyl chloride foam material for marine operations described in Comparative Example 1 is the same as that in Example 1, except that the raw material composition is different. The polyvinyl chloride foam material for marine operations described in Comparative Example 1, by weight, consists of the following raw materials: 100 parts polyvinyl chloride resin, 17 parts 1-(9,10-epoxyoctadecyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol, 4 parts oleic acid-modified Mg-Al-Zn ternary intercalated hydrotalcite, 39 parts 4,4'-diphenylmethane diisocyanate, 6 parts 4,4'-dicyclohexylmethane diisocyanate, 9 parts blowing agent, 2.7 parts di-tert-butyl peroxide, 2.5 parts heat stabilizer, 4 parts processing aid, 0.5 parts light stabilizer, and 0.4 parts antioxidant.
[0160] Comparative Example 2 The preparation method of the polyvinyl chloride foam material for marine operations described in Comparative Example 2 is the same as that in Example 1, except that the raw material composition is different. The polyvinyl chloride foam material for marine operations described in Comparative Example 2, by weight, consists of the following raw materials: 100 parts polyvinyl chloride resin, 7 parts silane-modified aluminum borate nanocrystals, 17 parts 1-(9,10-epoxyoctadecyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol, 39 parts 4,4'-diphenylmethane diisocyanate, 6 parts 4,4'-dicyclohexylmethane diisocyanate, 9 parts blowing agent, 2.7 parts di-tert-butyl peroxide, 2.5 parts heat stabilizer, 4 parts processing aid, 0.5 parts light stabilizer, and 0.4 parts antioxidant.
[0161] The performance of the polyvinyl chloride foam materials for marine operations prepared in Examples 1-3 and Comparative Examples 1-2 was tested. The density was tested according to ASTM D1622, the compressive strength according to ASTM D1621, the tensile strength according to ASTM D1623, and the water absorption rate after 48 hours of water pressure testing was measured. The salt spray test method involved continuous spraying for 1000 hours in a neutral salt spray environment as specified in GB / T 10125. The compressive strength of the samples was measured and the strength retention rate was calculated. The impact strength was tested according to the dart impact test method specified in GB / T 21333. The energy absorbed during impact failure was recorded, and the impact energy per unit area was converted to evaluate the material's impact resistance level based on the sample's stress area. Table 1 shows the test results. Table 1 Performance test results of polyvinyl chloride foam materials used in marine operations
[0162] As shown in Table 1, the performance of the polyvinyl chloride foam materials prepared in Examples 1-3 for marine operations is better than that in Comparative Examples 1-2. The performance of the polyvinyl chloride foam materials prepared in Comparative Examples 1-2 is reduced due to the lack of silane-modified aluminum borate nanocrystals and oleic acid-modified Mg-Al-Zn ternary intercalated hydrotalcite in the raw materials.
[0163] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A polyvinyl chloride foam material for marine operations, characterized in that: The product, by weight, is composed of the following raw materials: 100 parts polyvinyl chloride resin, 6-8 parts silane-modified aluminum borate nanocrystals, 16-18 parts 1-(9,10-epoxyoctadecyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol, 3.0-5.0 parts oleic acid-modified Mg-Al-Zn ternary intercalated hydrotalcite, 38-40 parts 4,4'-diphenylmethane diisocyanate, 5-7 parts 4,4'-dicyclohexylmethane diisocyanate, 8-10 parts foaming agent, 2.5-3.0 parts di-tert-butyl peroxide, 2.0-3.0 parts heat stabilizer, 3.0-5.0 parts processing aid, 0.5 parts light stabilizer, and 0.4 parts antioxidant. The preparation method of oleic acid modified Mg-Al-Zn ternary intercalated hydrotalcite consists of the following steps: ① Add borax solution and deionized water to a reaction vessel and mix well. Heat to 58-62℃, and simultaneously add mixed salt solution and sodium hydroxide solution dropwise while stirring, maintaining the pH of the system at 10.
0. After the addition is complete, heat the reaction system to 65℃ and continue stirring at a constant temperature of 65℃ for 2 hours. Then let it stand for 12 hours for aging. Filter, wash with deionized water until the pH of the filtrate is 7.0, vacuum dry, grind through a 200-mesh sieve, and prepare tetrahydroxyborate intercalated Mg-Al-Zn hydrotalcite. ② Tetrahydroxyborate-intercalated Mg-Al-Zn ternary hydrotalcite was added to anhydrous ethanol for ultrasonic dispersion, then heated to 65-70℃. Dilute hydrochloric acid was added dropwise to the dispersion to adjust the pH of the system to 5.5-6.
0. Oleic acid-ethanol solution was added dropwise while stirring. After the addition was complete, the mixture was stirred at 65-70℃ for 2.5 h. After the reaction was completed, the mixture was filtered. The filter cake was washed twice with anhydrous ethanol, then once with deionized water, and then once with anhydrous ethanol. The filter cake was vacuum dried, pulverized and sieved to prepare oleic acid-modified Mg-Al-Zn ternary intercalated hydrotalcite.
2. The polyvinyl chloride foam material for marine operations according to claim 1, characterized in that: The foaming agent is a mixture of azodicarbonamide, zinc oxide, and benzene-1,3-disulfonylhydrazine, wherein the mass ratio of azodicarbonamide, zinc oxide, and benzene-1,3-disulfonylhydrazine is 1.1:0.2:0.
3. The heat stabilizer is a mixture of calcium stearate, zinc stearate, pentaerythritol, and stearoyl benzoylmethane, wherein the mass ratio of calcium stearate, zinc stearate, pentaerythritol, and stearoyl benzoylmethane is 1.8 : 0.7 : 0.6 : 0.
3. The processing aid is a mixture of oxidized polyethylene wax and glyceryl monostearate, with a mass ratio of oxidized polyethylene wax to glyceryl monostearate of 4:
3. The light stabilizer is hindered amine light stabilizer HS-944, CAS number 70624-18-9; The antioxidant is a mixture of antioxidant 1010 and antioxidant 168, with a mass ratio of antioxidant 1010 to antioxidant 168 of 1:
1.
3. The polyvinyl chloride foam material for marine operations according to claim 1, characterized in that: The preparation method of 1-(9,10-epoxyoctadecanoyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol comprises the following steps: 9,10-epoxyoctadecanoic acid and toluene are added to a reaction apparatus, heated to 75-77°C and stirred until dissolved, then nitrogen is purged into the reaction apparatus for 30-35 minutes to replace the air inside the apparatus, hydroquinone monomethyl ether is added under nitrogen protection, the temperature is raised to 105-110°C, a mixture of triphenylphosphine-glycidyl methacrylate is added dropwise to the reaction system, and after the addition is complete, the mixture is stirred at a constant temperature of 105-110°C for 5.5 hours, heating is stopped, and the mixture is naturally cooled to 35°C under nitrogen protection. After post-treatment, 1-(9,10-epoxyoctadecanoyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol is obtained.
4. The polyvinyl chloride foam material for marine operations according to claim 3, characterized in that: In the preparation method of 1-(9,10-epoxyoctadecanoyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol, the mass of toluene accounts for 50% of the mass of 9,10-epoxyoctadecanoic acid; The nitrogen flow rate was 0.5 L / min, and the entire reaction and cooling process was carried out under nitrogen protection. Hydroquinone monomethyl ether accounts for 0.06% of the mass of glycidyl methacrylate; The addition time of the triphenylphosphine-glycidyl methacrylate mixture is 50-60 min. The triphenylphosphine-glycidyl methacrylate mixture is obtained by dissolving triphenylphosphine in glycidyl methacrylate and mixing it evenly. The mass of triphenylphosphine accounts for 0.4% of the total mass of 9,10-epoxyoctadecanoic acid and glycidyl methacrylate, and the molar ratio of 9,10-epoxyoctadecanoic acid to glycidyl methacrylate is 1:1.
13.
5. The polyvinyl chloride foam material for marine operations according to claim 3, characterized in that: The post-treatment method for preparing 1-(9,10-epoxyoctadecanoyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol involves diluting the crude product with toluene until the total mass of toluene is 1.5 times the mass of the crude product. The product is then filtered using a Buchner funnel to remove insoluble matter. The filtrate is transferred to a separatory funnel, and saturated NaHCO3 aqueous solution is added. The mixture is washed three times, with shaking for 10 seconds each time, followed by standing for 2 minutes to separate the layers. The volume of saturated NaHCO3 used in each wash is equal to the volume of the organic phase. After each shaking, the mixture is allowed to stand for 2 minutes to separate the layers. The lower aqueous phase is removed, and the upper organic phase is retained. The upper organic phase is transferred to a clean separatory funnel, and saturated NaCl aqueous solution is added. The volume of saturated NaHCO3 used in each wash is equal to the volume of the organic phase. The volume of the saturated NaCl aqueous solution was 1 times that of the organic phase. After shaking and washing once, the mixture was allowed to stand and separate into layers. The lower aqueous phase was removed, and the upper organic phase was retained. The upper organic phase was transferred to an Erlenmeyer flask, and anhydrous Na2SO4 (8% of the organic phase mass) was added and stirred. The mixture was dried at room temperature for 3 hours, filtered through a Buchner funnel to remove the Na2SO4 solid, and the organic phase filtrate was collected. The dried organic phase filtrate was then distilled under reduced pressure at a vacuum of -0.09 MPa, a temperature of 60 °C, and a time of 2 hours to prepare 1-(9,10-epoxyoctadecanoyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol.
6. The polyvinyl chloride foam material for marine operations according to claim 1, characterized in that: In the preparation method of oleic acid modified Mg-Al-Zn ternary intercalated hydrotalcite, the borax solution mentioned in step ① is an aqueous solution with a concentration of 0.25 mol / L prepared by dissolving Na2B4O7·10H2O in deionized water; In step ①, the mass ratio of borax solution to deionized water is 1:19-21; The stirring speed in step ① is 600 r / min; The mixed salt solution mentioned in step ① is prepared by dissolving Mg(NO3)2, Al(NO3)3, and Zn(NO3)2 in deionized water, with the three components arranged in the order of Mg(NO3)2, Al(NO3)3, and Zn(NO3)2. 2+ Al 3+ Zn 2+ The molar ratio of the metal ions added was 3:1:0.5, and the total concentration of metal ions in the mixed salt solution was 1.0 mol / L. In step ①, the concentration of the sodium hydroxide solution is 1.0 mol / L; During step ①, the pH value of the reaction system was monitored in real time, and the pH value of the system was maintained at 10.0 by adding 1.0 mol / L sodium hydroxide solution. In step ①, the vacuum drying temperature is 60℃ and the vacuum drying time is 12h; In step ②, the mass ratio of tetrahydroxyborate-intercalated Mg-Al-Zn ternary hydrotalcite to anhydrous ethanol is 1:5-8; In step ②, the concentration of dilute hydrochloric acid is 0.1 mol / L; In step ②, the mass ratio of tetrahydroxyborate-intercalated Mg-Al-Zn ternary hydrotalcite to oleic acid is 1:0.1-0.12; In step ②, the mass ratio of oleic acid to anhydrous ethanol in the oleic acid-ethanol solution is 1:4; In step ②, the ultrasonic dispersion power is 300W, the ultrasonic dispersion time is 5-10min, and the stirring speed is 800r / min; In step ②, the oleic acid-ethanol solution is added dropwise over a period of 20-25 minutes. In step ②, the vacuum drying temperature is 70℃ and the vacuum drying time is 8h. After air jet pulverization, the product is passed through a 600-mesh sieve.
7. The polyvinyl chloride foam material for marine operations according to claim 1, characterized in that: The preparation method of silane-modified aluminum borate nanocrystals consists of the following steps: (i) Aluminum borate nanocrystals are vacuum dried at 120℃ for 4h to obtain dried whiskers; (ii) Anhydrous ethanol and water are mixed, glacial acetic acid is added to adjust the pH of the system to 4.7, KH-550 silane coupling agent is added, and the mixture is stirred and hydrolyzed at 25℃ for 30min to obtain a hydrolysate; (iii) The dried whiskers obtained in step (i) are added to the hydrolysate, and the mixture is stirred and reacted at 67℃ for 2.5h. Then the reaction solution is pulsed and sonicated, and finally vacuum filtered, washed 3 times with anhydrous ethanol, vacuum dried at 85℃ for 3h, and pulverized through a 600-mesh sieve to obtain silane-modified aluminum borate nanocrystals; In step (ii), the volume ratio of anhydrous ethanol to water is 92:8, and the mass of KH-550 silane coupling agent accounts for 2.5% of the mass of the dried whiskers prepared in step (i). In step (3), the pulsed ultrasound power is 400W, the operation lasts 2 seconds and stops for 1 second, and the ultrasound time is 15 minutes.
8. A method for preparing a polyvinyl chloride foam material for marine operations as described in claim 1, characterized in that: It consists of the following steps: (1) Polyvinyl chloride resin, silane-modified aluminum borate nanocrystals, oleic acid-modified Mg-Al-Zn ternary intercalated hydrotalcite, heat stabilizer, processing aid, light stabilizer and antioxidant are added to a high-speed mixer and mixed. The mixture is cooled to 60-65℃ and 1-(9,10-epoxyoctadecyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol is added and mixed. The mixture is then cooled to 45-50℃ and foaming agent and di-tert-butyl peroxide are added and mixed. Finally, the mixture is cooled to 35-40℃ and 4,4'-diphenylmethane diisocyanate and 4,4'-dicyclohexylmethane diisocyanate are added and mixed. The mixture is then discharged to obtain the mixture. (2) Place the mixture in a mold, pressurize it to 15MPa, keep it at a constant temperature of 168-172℃ for 18-20min, and open the mold after cooling to prepare a pre-foamed blank; (3) Place the pre-foamed blank in a saturated steam treatment vessel, pre-evacuate to -0.05MPa and maintain for 8min, then introduce saturated steam to the gauge pressure of 0.05MPa, treat at 110-112℃ for 20min, then cool down to 60℃ at a rate of 3℃ / min, and release the pressure from the vessel. (4) The steam-treated foam blank is placed in a constant temperature curing oven at 75-80℃ for curing, and then slowly cooled to room temperature at a rate of 3℃ / h to prepare polyvinyl chloride foam material for marine operations.
9. The method for preparing polyvinyl chloride foam material for marine operations according to claim 8, characterized in that: In step (1), polyvinyl chloride resin, silane-modified aluminum borate nanocrystals, oleic acid-modified Mg-Al-Zn ternary intercalated hydrotalcite, heat stabilizer, processing aid, light stabilizer, and antioxidant are added to a high-speed mixer and stirred at 96-100℃ and 1100r / min for 8-12 minutes. The mixture is then cooled to 60-65℃, and 1-(9,10-epoxyoctadecyloxy)-3-(2-methylprop-2-enoyloxy)prop-2-ol is added and stirred for 3-5 minutes. The mixture is then cooled to 45-50℃, and foaming agent and di-tert-butyl peroxide are added and stirred for 2-3 minutes. Finally, the mixture is cooled to 35-40℃, and 4,4'-diphenylmethane diisocyanate and 4,4'-dicyclohexylmethane diisocyanate are added and stirred for 2 minutes. The mixture is then discharged to obtain the final product. The mold body to be opened after cooling in step (2) is to be cooled to 60°C at a rate of 3°C / min before opening the mold; The maturation time in step (4) is 72 hours.
Citation Information
Patent Citations
High-density hard cross-linked polyvinyl chloride foam and preparation method thereof
CN116199990A
PVC foam used as offshore buoyancy material and preparation method thereof
CN113321881A
Formulations for Cellular, Foamed-Polymer Products Based on Polyvinyl Chloride,Improved Cellular, Foamed-Polymer Products Based on Polyvinyl Chloride and a Process for Producing Said Improved Cellular Foamed-Polymer Products
US20100068487A1